Implementation of the P5 Program Based on Cadet Education at SMAN 14 Bandung - Agnevia Nursianda; Rahma Agustina Fadhilah; Elva Hanov Rais; Ahnaf Daris Fadhilah (COMPETITIVE: Journal of Education, 2025)
This study aims to understand the implementation of the Pancasila Student Profile Strengthening Project (P5) based on cadets at SMAN 14 Bandung as part of the implementation of the Merdeka Curriculum. The research method used is descriptive qualitative with data collection techniques through in-depth interviews, observation, and documentation. The research subjects involved the vice principal for curriculum, teachers, and students of SMAN 14 Bandung. The results of the study show that the cadet program at SMAN 14 Bandung has systematic implementation stages, starting from assembly activities, materialization, basic leadership training, to the inauguration of male and female cadets. This program aims to shape the character of students through the values ​​of discipline, independence, and responsibility. In addition, this program has succeeded in creating a conducive school environment, increasing student participation in school activities, and forming characters that are in accordance with the Pancasila student profile. Character education through P5 based on cadets has a positive influence on students, both in the development of morals, ethics, and social skills. This program also creates educational innovations that focus on developing students' character and competencies holistically, making them better prepared to face the challenges of modern life with an independent, critical, and integrity-based attitude.